CO2 photoreduction at enzyme-modified metal oxide nanoparticles - Woolerton, T; Sheard, S; Pierce, E; Ragsdale, S; Armstrong, F (2011)
A model system for photoreduction of CO2 to CO using visible light has been extensively studied, using a catalyst for which the CO 2/CO reaction is electrochemically reversible. The hybrid system comprises metal oxide nanoparticles functionalised with the enzyme carbon monoxide dehydrogenase (CODH), and sensitised to visible light using a ruthenium bipyridyl photosensitiser. An anatase/rutile TiO2 mixture (Evonik Degussa P25) was selected as the most suitable semiconductor, and CO production rates and stability were examined as a function of each component (photosensitiser, enzyme and TiO2). Tolerance to O2 and effects of different electron donors were also investigated, together with strategies to control enzyme binding at the surface of TiO2 in order to enhance overall activity. © 2011 The Royal Society of Chemistry.